Hubungan Antara Parent Child Communication Dengan Brain Rot Pada Generasi Z - Putri, Esterlina Melati Dessan (Publikasi Indonesia, 2025)
he phenomenon of Brain Rot has emerged as a new concern in adolescent psychology, especially among Generation Z who are highly immersed in the digital world. Brain Rot describes a condition of mental fatigue and cognitive decline due to excessive exposure to digital content. This study aims to examine the relationship between Parent-Child Communication and Brain Rot in Generation Z, as well as to analyze the influence of each communication aspect. Using a quantitative approach and purposive sampling technique, the study involved 207 participants who actively use social media and live with their parents. Instruments included a Brain Rot scale developed by the researcher and the Parent–Child Communication Quality Scale (Lyu dkk., 2024). Spearman’s correlation analysis revealed a significant negative relationship between Parent-Child Communication and Brain Rot (r = -0.217; p = 0.002). Linear regression analysis found that only one aspect—parental emotional involvement—significantly influenced Brain Rot. However, the overall contribution of the independent variable to Brain Rot was relatively low (R² = 6.9%). These findings suggest that emotional communication within families serves as a protective factor against the negative effects of digitalization, and may serve as a basis for further research and intervention.